2017
DOI: 10.1093/mnras/stx1222
|View full text |Cite
|
Sign up to set email alerts
|

Radio polarization maps of shell-type SNRs – II. Sedov models with evolution of turbulent magnetic field

Abstract: Polarized radio emission has been mapped with great detail in several Galactic supernova remnants (SNRs), but has not yet been exploited to the extent it deserves. We have developed a method to model maps of the Stokes parameters for shell-like SNRs during their Sedov evolution phase. At first, 3-dimensional structure of a SNR has been computed, by modeling the distribution of the magnetohydrodynamic parameters and of the accelerated particles. The generation and dissipation of the turbulent component of magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…The authors demonstrated that radio-emitting electrons accelerated at quasi-parallel shocks can have spatial distributions that result in an apparent radial magnetic field in radio synchrotron maps even when the field is in fact disordered. Bandiera & Petruk (2016) and Petruk et al (2017) modeled radio images of SNRs accounting for turbulent magnetic fields.…”
Section: )mentioning
confidence: 99%
“…The authors demonstrated that radio-emitting electrons accelerated at quasi-parallel shocks can have spatial distributions that result in an apparent radial magnetic field in radio synchrotron maps even when the field is in fact disordered. Bandiera & Petruk (2016) and Petruk et al (2017) modeled radio images of SNRs accounting for turbulent magnetic fields.…”
Section: )mentioning
confidence: 99%
“…SNRs have a long history of polarization models for the radio band, and such models have attempted to constrain the origin of the observed polarization dichotomy, including recipes to relate it to the physics of acceleration [15,36]. More recently, the same technique used to include the effects of a turbulent component in the emission of PWNs have been applied to shell SNRs, trying to derive possible observational constraints to locate the regions where the turbulence is higher, and to assess its correlation with particle acceleration sites [51]. One of the most interesting aspects of X-ray emission in SNRs is that it takes place close to the cut-off regime: this implies that emission tends to weigh regions of higher magnetic fields to a greater extent, and this means that large differences in the polarized emission pattern are expected for shallow vs. steep magnetic turbulent spectra.…”
Section: Polarization Modelsmentioning
confidence: 99%
“…Based on the idea that small-scale turbulence can be present, we have developed a formalism to include it, as a sub-grid effect [50][51][52], into large scale models for the global structure of the field, either simplified toy models on the line of [53], which are easy and fast to compute and allow us to deeply scan the possible parameter space in order to optimize the agreement with observations, or more sophisticated time-dependent numerical models that can take into account the interplay between the pulsar wind and the environment. These models have been recently applied to the Crab and Vela nebulae [52].…”
Section: Polarization Modelsmentioning
confidence: 99%
“…It is used in cases where one needs to calculate SNR synchrotron emission (e.g. Chevalier 1974;Reynolds 1998;Petruk et al 2017). It is based on the equations for magnetic field (see references in section 2.2 in Petruk, Kuzyo & Beshley 2016) applied to the spatial SNR structure derived from the HD solutions or simulations.…”
Section: Introductionmentioning
confidence: 99%